Meningeal T cells function in the central nervous system homeostasis and neurodegenerative diseases - Abbaoui, Abdellatif; Fatoba, Oluwaseun; Yamashita, Toshihide (Frontiers in Cellular Neuroscience, 2023)
Recently, a rising interest is given to neuroimmune communication in physiological and neuropathological conditions. Meningeal immunity is a complex immune environment housing different types of immune cells. Here, we focus on meningeal T cells, possibly the most explored aspect of neuro-immune cell interactions. Emerging data have shown that meningeal T cells play a crucial role in the pathogenesis of several neurodegenerative disorders, including Multiple sclerosis, Alzheimer's, Parkinson's, and Huntington's diseases. This review highlights how meningeal T cells may contribute to immune surveillance of the central nervous system (CNS) and regulate neurobehavioral functions through the secretion of cytokines. Overall, this review assesses the recent knowledge of meningeal T cells and their effects on CNS functioning in both health and disease conditions and the underlying mechanisms.